A Study of Negative Impulsive Wave Generator for Reducing Impulsive Noise : Model Testing of a Generator Utilizing Unsteady Mass Influx - Tsujimoto, Yoshikazu; Aoki, Toshiyuki; Iwamoto, Kengo; Setoguchi, Toshiaki; Kaneko, Kenji; Matsuo, Kazuyasu; Kita, Nobuyuki (Nihon Kikai Gakkai rombunshuu. B hen, 1995)
The compression wave discharged from an open end of a tube causes positive impulsive noise. Active noise cancellation, which is the cancelling of the noise by the addition of an inverse wave, is a useful technique for reducing impulsive noise. The objective of this study is to present a design for a negative impulsive wave generator utilizing unsteady mass influx. The generator consists of a vacuum chamber and a movable valve. From experimental investigations, the relation between the valve behavior and the characteristics of the negative impulsive wave has been clarified, and a suitable choice of the design factors has been suggested.